Impact of Surgery on Older Patients Hospitalized With an Acute Abdomen: Findings From the Older Persons Surgical Outcome Collaborative - Tay, Hui Sian; Wood, Adrian D.; Carter, Ben; Pearce, Lyndsay; McCarthy, Kathryn; Stechman, Michael J.; Myint, Phyo K.; Hewitt, Jonathan (Frontiers in Surgery, 2020)
Background: The impact of surgical operation on older people presenting as general surgical patients compared to non-surgical management is less well researched. Methods: We examined the association between management and adverse outcomes in a cohort of emergency general surgery patients aged>65 years. This multi-center study included 727 patients (mean+/-SD, 77.1±8.2 years, 54% female) admitted to five UK hospitals. Data were analyzed using multi-level crude and multivariable logistic regression. Outcomes included: mortality at Day 30 and 90, length of stay, and readmission within 30 days of discharge. Covariates assessed were management approach, age, sex, frailty, polypharmacy, anemia, and hypoalbuminemia. Results: Approximately 25% of participants (n=185) underwent emergency surgery. Frailty and albumin were associated with mortality at 30 (frailty OR=3.52 [95%CI 1.66-7.49], albumin OR=3.78 ([95%CI 1.53-9.31]), and 90 days post discharge (frailty OR=3.20 [95%CI 1.86-5.51], albumin OR=3.25 [95%CI 1.70-6.19]) and readmission (frailty OR=1.56 [[95%CI (1.04-2.35)]. Surgically managed patients and frailty had increased odds of prolonged hospitalization (surgery OR=5.69 [95%CI 3.67-8.80], frailty OR=2.17 [95%CI 1.46-3.23]). Conclusion: We found the impact of surgery on length of hospitalisation in older surgical patients is substantial. Whether early comprehensive geriatric assessment and post-op rehabilitation would improve this outcome require further evaluation. Keywords: acute surgery, length of stay, mortality, older patients, operation, readmission